PERANCANGAN APLIKASI PAKET WISATA BERBASIS WEB - Indah Puji Astuti; Yayan Fatrurrohman; Muhammad Masykuri; Nur Ahmad Syarifudin (MULTITEK INDONESIA, 2018)
The technological development in this world, especially the Internet is growing so fast. The Internet has changed some even almost the entire lifestyle of society. This has an impact on people's behavior, for example in the search for information, people are starting to leave a manual search process that take a long time to get the information and move on to use of the Internet to get the information quickly. The number of cities in East Java amount to 38 cities. Each city has an interesting tourist attraction to visit. However, one of the problem for local governments in terms of tourism development is there is no an effective and efficient Information System for tourism. To solve this problem, required an application that can facilitate the tourists in finding information about tourism and reservation hotel and travel. In this research has designed a web-based TRAVVIN application that is expected to facilitate tourists in the search information on tourist attractions, especially in East Java. In this research adopted from the stages of system development with waterfall method, consists of analysis stage and design stage. The result of this research is an analysis and design document.